Mitochondria-Associated Endoplasmic Reticulum Membranes: Inextricably Linked with Autophagy Process. (23rd August 2022) - Ji, Chonghao; Zhang, Zhanwei; Li, Zechuan; She, Xiao; Wang, Xiaoya; Li, Binyang; Xu, Xin; Song, Dawei; Zhang, Dongjiao
Abstract : Mitochondria-associated membranes (MAMs), physical connection sites between the endoplasmic reticulum (ER) and the outer mitochondrial membrane (OMM), are involved in numerous cellular processes, such as calcium ion transport, lipid metabolism, autophagy, ER stress, mitochondria morphology, and apoptosis. Autophagy is a highly conserved intracellular process in which cellular contents are delivered by double-membrane vesicles, called autophagosomes, to the lysosomes for destruction and recycling. Autophagy, typically triggered by stress, eliminates damaged or redundant protein molecules and organelles to maintain regular cellular activity. Dysfunction of MAMs or autophagy is intimately associated with various diseases, including aging, cardiovascular, infections, cancer, multiple toxic agents, and some genetic disorders. Increasing evidence has shown that MAMs play a significant role in autophagy development and maturation. In our study, we concentrated on two opposing functions of MAMs in autophagy: facilitating the formation of autophagosomes and inhibiting autophagy. We recognized the link between MAMs and autophagy in the occurrence and progression of the diseases and therefore collated and summarized the existing intrinsic molecular mechanisms. Furthermore, we draw attention to several crucial data and open issues in the area that may be helpful for further study.